New Chiral and Achiral Imines and Bisimines Derived from 2-Phenyl-1H-imidazole-4-carbaldehyde. Synthesis, Structural Studies and Complexation Stability Constants - Parik, P.; Chlupaty, T. (Journal of heterocyclic chemistry, 2014)
Synthesis and properties of new imines and bisimines derived from 2‐phenyl‐1H‐imidazole‐4‐carbaldehyde and amines/diamines were studied. (2‐Phenyl‐1H‐imidazole‐4‐yl)methanol was oxidized to 2‐phenyl‐1H‐imidazole‐4‐carbaldehyde with better yield 55% by the modification of literature procedure. This aldehyde was condensed with the following achiral and chiral amines or 1,2‐diamines: ethanamine, propan‐1‐amine, butan‐1‐amine, 2‐methylpropan‐1‐amine, cyclohexanamine, (2R)‐ and (2S)‐3‐methylbutan‐2‐amine, (1R)‐ and (1S)‐1‐cyclohexylethanamine, (S)‐1‐aminopropan‐2‐ol, (S)‐1‐(2‐phenyl‐1H‐imidazol‐4‐yl)ethanamine, (S)‐1‐(2‐phenyl‐1H‐imidazol‐4‐yl)‐2‐methylpropan‐1‐amine, (S)‐1‐(2‐phenyl‐1H‐imidazol‐4‐yl)‐3‐methylbutan‐1‐amine, ethane‐1,2‐diamine, and (1R,2R)‐ and (1S,2S)‐cyclohexane‐1,2‐diamine. Sixteen condensation products, especially chiral imines and bisimines, were prepared by founded procedures in 45–99% of yields and characterized by the 1H NMR spectroscopy in solution, mass spectrometry, and elemental analyses. The optical rotation values in the case of chiral ones were also observed. Stability constants of Cu(II) complexes of selected prepared imines/bisimines were determined.